Compulsory staff registers as a way of increasing firms' wage reporting: A revenue-cost analysis - Sven-Olov Daunfeldt; Anton Gidehag; Niklas Rudholm (Institute of Retail Economics (HFI), 2019)
In 2007, the Swedish government tried to prevent firms from underreporting their wage payments by implementing a reform that required restaurants and hairdressers to have staff registers. Employers were required to provide detailed information on when their employees were working, and the Swedish Tax Authority was also given a mandate to carry out unannounced control visits and to impose fines on firms that had not properly filled out their staff registers. We estimate the effect of this reform on firms' wage reporting using propensity score matching combined with a difference-in-differences analysis. Then, we compare the increase in tax revenues with the costs that the staff register system generated for the firms and the Swedish Tax Authority. Our results show that the total costs of the system exceeded the increase in tax revenues by approximately 355 million SEK (36.6 million) over a four-year period, even when utilizing point estimates that are likely to overstate the effect on wage reporting. We thus conclude that considering the costs associated with the reform, the staff register reform is not economically justified.
Keywords: H26; H32; K34; L51; 330; tax evasion; firm regulation; quasi-experimental method; unreported wages; propensity score matching